Population flux of the house sparrow Passer domesticus Linnaeus 1758 in Chinnamanur town, Uthamapalayam taluk of Theni district, Tamil Nadu, India - Mohamed Meeran; Syed Marjuk; Mohammed Byrose; Subramanian Arivoli; Samuel Tennyson; Syedali Fathima (Journal of Tropical Life Science, 2021)
A thorough study of house sparrow behaviour and its population is essential to revive its population status which is the need of the hour. Therefore, the nature of sparrow population, their nests, water and food sources, interspecific competitions and noise pollution were taken into consideration in the present investigation, which documented its first research carried at Chinnamanur town, Uthamapalayam taluk of Theni district, Tamil Nadu, India. The study period was divided into summer and winter seasons and the survey was carried out for a period of nine months from April 2019 to December 2019 by point count and ebird data method. A total of 542 house sparrows were counted of which 250 was present in summer and 292 in winter. The overall house sparrow population in Chinnamanur town, related to the summer and winter seasons exhibited the range of correlation coefficient value to be 0.94 indicating a very strong positive correlation. Above all, the present study revealed that mobile phone towers were not the main reason for the decline of house sparrows, rather it was loss of habitat and food, urbanization, noise pollution, interspecific competition and conversion of agricultural lands into plots.